2002
DOI: 10.1590/s1516-89132002000600001
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis in soybeans for seed yield components and associated traits

Abstract: The objective of this research was to quantify heterosis of agronomic traits and evaluate direct and indirect correlations among seed yield and other traits. A diallel involving six parents was grown in two localities. Seed yield (PG), one-hundred seed weight (PCS), number of pods per plant (NV), weight of aerial part of the plant (PPA), harvest index (IC) and number of seeds per pod (NGV) were evaluated. Positive values of heterosis were detected for all traits. Estimates of heterosis components were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 6 publications
0
21
0
3
Order By: Relevance
“…This connection can be explained by the translocation of photosynthates to produce higher number of pods which implies the portion of these which will be translocated to the grains will be smaller. Pandini et al (2002) evaluated correlations between traits in soybean and reported the character number of pods per plant have potential for indirect selection of more productive genotypes. According to these authors, the characters of agronomic value may be correlated in different magnitudes.…”
Section: Resultsmentioning
confidence: 99%
“…This connection can be explained by the translocation of photosynthates to produce higher number of pods which implies the portion of these which will be translocated to the grains will be smaller. Pandini et al (2002) evaluated correlations between traits in soybean and reported the character number of pods per plant have potential for indirect selection of more productive genotypes. According to these authors, the characters of agronomic value may be correlated in different magnitudes.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the number of pods plot -1 was the trait of strongest direct influence (1.179) in a favorable sense on the grain yield; this trait should therefore be considered when aiming at the selection of productive genotypes. In soybean, the number of pods plant -1 also presented a potential for indirect selection of genotypes with higher yield (Pandini et al 2002). According to Wynne and Coffelt…”
Section: Resultsmentioning
confidence: 99%
“…The partitioning of the coefficient of correlation by the path analysis, developed initially by Sewall Wright according to Li (1956), consisted in the study of the direct and indirect effects of traits on a basic variable, whose estimates are obtained by regression equations in which the variables are previously standardized. Knowledge on the direct and indirect correlations, especially of the yield, allows breeders to use this additional information to discard or promote genotypes of interest (Pandini et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge of direct and indirect correlations about determined yield component, especially grain yield, enables the breeder to use this additional information to precisely discard or promote the genotypes of interest (Pandini et al, 2002). The correlation between traits allows the indirect selection of a quantitative trait of difficult gain with selection, through the selection of another trait directly correlated to it, with greater genetic gain or easy visual selection (Pipolo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%